AWE-08 Why are we missing colorectal cancer? A study investigating the cause of delays in diagnosis. Issue 2 (June 2019) - Hayes, B; Bjarnason, I; Logan, R; Hayee, B; Dubois, P; Haji, A; Barker, Lindsey; Chung-Faye, G; Srirajaskanthan, R; Kent, AJ
Abstract : Introduction: Delay in diagnosis of colorectal cancer (CRC) is associated with worse outcomes. Although studies have shown the incidence of CRC missed at endoscopy to be 2.5%-7.7% ( Morris et al., 2014), there are additional non-endoscopic factors that may lead to delays. This study aimed to identify all factors leading to a delayed diagnosis, including endoscopic "misses". Methods: All patients diagnosed with CRC at Kings College Hospital, London between 2011 – 2018 were included. We identified patients seen in an outpatient clinic or underwent endoscopy within 36 months preceding diagnosis. 'Delayed' cancers were grouped into 'clinical factors' and 'technical factors'. 'Clinical factors' included the subset of post-colonoscopy colorectal cancers (PCCRC). The Joint Advisory Group on GI endoscopy (JAG) have defined PCCRC as being cancers diagnosed within 36 months of an endoscopy. Results: 797 cases of CRC were diagnosed in the study period and 60(7.5%) were seen in the preceding 36 months. 46 patients (5.8%) were determined to have a delayed diagnosis, of which 24(52.2%) were diagnosed within 1 year of initial investigation. 38 delayed diagnoses were due to clinical factors: PCCRC (n=23), incomplete endoscopy (n=2), inadequate investigation (n=7), missed on rigid sigmoidoscopy (n=1) and incomplete bowel preparation (n=5) with an average delay of 172 days. 8 delays were caused by technical factors: Incomplete follow up (n=4), delayed investigation (n=2), histology not reviewed (n=1), missed on CT (n=1). The rate of missed cancer in the 2WW, Bowel Cancer Screening and Routine referral pathways was 4.8% (n=14), 5.1% (n=8), 7.3% (n=28) respectively. The incidence of missed cancer in the right colon was significantly higher (p=0.068, 95% CI 0.9–.57). Further interrogation showed the highest incidence in the hepatic flexure (10.5%), splenic flexure (9.4%), caecum (7.5%), and anal canal (6.5%). 91.3% of PCCRCs versus 47.8% of other missed cancers identified another pathology at the initial endoscopy which was documented on the report (p=0.003, 95% Confidence interval 2.1–0.6). A delay in diagnosis was not associated with more advanced TNM staging or K-ras mutations. Conclusions: Our rate of missed cancers is equivalent to that published in the literature, with the majority of missed cancers due to PCCRC. Delays in diagnosis are related to avoidable factors, such as improving the quality of bowel prep or ensuring further investigations in patients with incomplete endoscopies. Endoscopists should also be aware of the increased miss rate in specific locations. Non-cancer pathology identified at endoscopy is also associated with missed cancer, so endoscopists should be careful to maintain a careful examination for concomitant cancers.